Liquidity risk and interdependence in payment systems: The case of Peru - Jushua Baldoceda; Anthony Meza (Graduate Institute of International and Development Studies, 2022)
The failure of a financial institution (banks and microfinance institutions) to meet its payment obligations can have implications, not only for its continuity, but also for the stability of payment systems, markets, and the financial system in general. Central banks, as monetary authorities, regulators, and overseers of a country's payment infrastructures must monitor the liquidity risk of participants in those systems in order to prevent in time any event of this nature. To do this, the liquidity needs of the entities must be identified and anticipated to mitigate the possible effects of their inability to pay and the possible consequences on the payment systems. This paper reviews the literature on liquidity risks and their systemic consequences. It also presents different indicators of liquidity and interdependence built with the transactional data of the RTGS System, administered by the Central Reserve Bank of Peru. These indicators are contrasted with the participant's intraday facilities operations in the RTGS (from Jan-2010 to Nov-2021), in order to assess the liquidity problem and its consequences from a systemic point of view.
Keywords: E42; E50; E58; 330; RTGS; liquidity risk; systemic risk; indicators